Calidad de vida y salud oral en el adulto mayor del centro del adulto mayor del hospital III EsSalud - Iquitos, 2024 - Carranza del Aguila, Raúl (2025)
The objective of the study was to determine the relationship between quality of life and oral health of the elderly in the Senior Center of Hospital III EsSalud – Iquitos. Methodology: non-experimental, quantitative, cross-sectional and correlational. A sample of 80 elderly people from the Senior Center of Hospital III EsSalud – Iquitos was used. Hospital III EsSalud – Iquitos. Results: The level of perception of quality of life of the elderly at the Senior Citizens Center of Hospital III EsSalud - Iquitos, 2024 was low with 67.5%, after applying the GOHAI, while it was Regular (Neither so good nor so bad), with 86.3% according to WHOQOL - OLD. 57.5% of older adults turned out to have a low perception of quality of life according to the GOHAI and a regular quality of life according to WHOQOL - OLD. Conclusion: The P value obtained in the Spearman Rho test for the variables quality of life and oral health was (p = 0.205), which reflects that there is no significant relationship between them.